Konsep Ruang dalam Metafora pada Bahasa Mandailing: Kajian Semantik Koognitif - Adipati, M YUS; Mulyadi, Mulyadi (Universitas Muhammadiyah Surabaya, 2025)
This paper explains the conceptualization of space in metaphors in the Mandailing language. The author utilizes the cognitive semantic conceptual study by Lakoff and Johnson (1980), further elucidated by Cruse & Croft (2004) and Saeed (2009) in describing and analyzing data. It generates spatial concepts referring to the concepts of experts, including the concept of space-time according to Lakoff and Johnson, the concept of positional/location space according to Max Black, the concept of space according to Donald Davidson, then grouped according to expert concepts into the Mandailing language and provided explanations or meanings of the conceptually generated metaphors.